New Insights into IDO Biology in Bacterial and Viral Infections - Schmidt, Susanne V.; Schultze, Joachim L. (Frontiers in Immunology, 2014)
Initially, IDO has been introduced as a bactericidal effector mechanism and has been linked to T cell immunosuppression and tolerance. In recent years, evidence has been accumulated that IDO also plays an important role during viral infections including HIV, influenza and hepatitis B and C. Moreover, novel aspects about the role of IDO in bacterial infections and sepsis have been revealed. Here we review these recent findings highlighting the central role of IDO and tryptophan metabolism in many major human infections. Moreover, we also shed light on issues concerning human-specific and mouse-specific host - pathogen interactions that need to be considered when studying the biology of IDO in the context of infections.